Identificación de los agentes bacterianos Salmonella sp., Shigella sp., Escherichia coli, Staphylococcus sp., Klebsiella sp., Citrobacter sp., Pseudomonas sp., Enterobacter sp, Proteus sp., relacionados con la mortalidad en cuyes hembras reproductoras (Cavia porcellus) de crianza intensiva en la explotación Cuyera Andina ubicada en la provincia de Imbabura - Ibarra Estévez, Emerson Roberto (2023)
The production of guinea pigs is classified as one of the most important activities for families and producers from the Ecuadorian highlands, however, the presence of certain diseases within the farms prevents an adequate development of the animals, thus reproducing directly to their production and reproduction, also increasing a total imbalance by increasing mortality rates. One of the main causes of this problem is the inadequate and scarce or even null use of sanitary programs within the facilities, allowing the entry and proliferation of bacterium, which, in turn, will generate diseases throughout the shed. A solution to this is the implementation of prevention plans and staff training, as well as the first instance, the identification of the main bacterial agents associated with the mortality of guinea pigs. The general objective of this study is focused on determining the presence of strains such as Salmonella sp., Shigella, Escherichia coli., Staphylococcys sp., Klebsiella sp., Citrobacter sp., Pseudomonas sp., Enterobacter sp. and Proteus sp. For the development of the research, two stages were contemplated, the selection and collection of animals in the Cuyera Andina farm and the carrying out of the tests in the laboratories of the Pontifical Catholic University of Ecuador in Ibarra. In the investigation, the descriptive statistics method was applied, with which the incidence of bacteria in both liver and lung will be determined, as well as the positives and negatives for the months of study. The result of this research was evidenced in the development of the prevention plan that allowed for greater knowledge regarding the bacterium found within the farm and with which to establish a disease control program. The study carried out shows that the climatic season and the evaluation period influence the presence of bacterial agents to a greater or lesser extent.